The Effect of Gimkit Media on Elementary Students’ Critical Thinking Skills in Science Learning - Putri, Azlia Anugerah; Sari, Prima Mutia (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
This study examines the effectiveness of Gimkit, a game-based interactive learning platform, in enhancing the critical thinking skills of fourth-grade elementary students within the context of science education. Addressing the limited development of higher-order thinking skills at the elementary level, this research aimed to determine whether integrating digital media such as Gimkit can significantly improve students’ critical thinking performance. Utilizing a quantitative approach and a quasi-experimental design with a nonequivalent control group, the study involved 54 students divided evenly between experimental and control classes. The experimental group received instruction supported by Gimkit, while the control group followed conventional teaching methods. Critical thinking skills were measured using a validated test instrument encompassing four key indicators: analyzing information, formulating problems, drawing conclusions, and evaluating data. Data were analyzed using an independent samples t-test, which revealed a statistically significant difference between the post-test scores of the two groups (p < .001). The effect size, as measured by Cohen’s d = 2.118, reflects a very large impact. Students in the experimental group showed substantial gains across all critical thinking indicators. These results highlight the potential of structured, game-based digital tools to foster cognitive engagement and skill development in elementary science instruction. In short, the findings carry practical implications for the design of instructional strategies that incorporate educational technology to support critical thinking from an early age.